Cytosolic p53 Inhibits Parkin-Mediated Mitophagy and Promotes Acute Liver Injury Induced by Heat Stroke - Huang, Wei; Xie, Weidang; Zhong, Hanhui; Cai, Shumin; Huang, Qiaobing; Liu, Youtan; Zeng, Zhenhua; Liu, Yanan (Frontiers in Immunology, 2022)
Heat stroke (HS) is a severe condition characterized by increased morbidity and high mortality. Acute liver injury (ALI) is a well-documented complication of HS. The tumor suppressor p53 plays an important role in regulation of mitochondrial integrity and mitophagy in several forms of ALI. However, the role of p53-regulated mitophagy in HS-ALI remains unclear. In our study, we discovered the dynamic changes of mitophagy in hepatocytes and demonstrated the protective effects of mitophagy activation on HS-ALI. Pretreatment with the mitophagy inhibitor 3-MA significantly exacerbated ALI by inhibiting mitophagy in HS-ALI mice. Consistent with the animal HS-ALI model results, silencing Parkin aggravated mitochondrial damage and apoptosis by inhibiting mitophagy in HS-treated normal human liver cell line (LO2 cells). Moreover, we described an increase in the translocation of p53 from the nucleus to the cytoplasm, and cytosolic p53 binds to Parkin in LO2 cells following HS. p53 overexpression using a specific adenovirus or Tenovin-6 exacerbated HS-ALI through Parkin-dependent mitophagy both in vivo and in vitro, whereas inhibition of p53 using siRNA or PFT-α effectively reversed this process. Our results demonstrate that cytosolic p53 binds to Parkin and inhibits mitophagy by preventing Parkin’s translocation from the cytosol to the mitochondria, subsequently preventing the ubiquitination of VDAC. Overall, pharmacologic induction of mitophagy by inhibiting cytosolic p53 may be a promising therapeutic approach for HS-ALI treatment.